Purinergic System Signaling in Metainflammation-Associated Osteoarthritis - Gratal, Paula; Lamuedra, Ana; Medina, Juan Pablo; Bermejo-Álvarez, Ismael; Largo, Raquel; Herrero-Beaumont, Gabriel; Mediero, Aránzazu (Frontiers in Medicine, 2020)
Inflammation triggered by metabolic imbalance, also called metainflammation, is low-grade inflammation caused by the components involved in metabolic syndrome (MetS), including central obesity and impaired glucose tolerance. This phenomenon is mainly due to excess nutrients and energy, and it contributes to the pathogenesis of osteoarthritis (OA). OA is characterized by the progressive degeneration of articular cartilage, which suffers erosion and progressively becomes thinner. Purinergic signaling is involved in several physiological and pathological processes, such as cell proliferation in development and tissue regeneration, neurotransmission and inflammation. Adenosine and ATP receptors, and other members of the signaling pathway, such as AMP-activated protein kinase (AMPK), are involved in obesity, type 2 diabetes (T2D) and OA progression. In this review, we focus on purinergic regulation in osteoarthritic cartilage and how different components of MetS, such as obesity and T2D, modulate the purinergic system in OA. In that regard, we describe the critical role in this disease of receptors, such as adenosine A2A receptor (A2AR) and ATP P2X7 receptor. Finally, we also assess how nucleotides regulate the inflammasome in OA.